Teacher Competencies for the Use of Information Communication Technology - Husain, Noushad (JOURNAL OF INDIAN EDUCATION, 2010)
The Present study aimed to identify the competencies needed by teachers for development and implementation of Information Communication Technology (ICT)- based education. Survey method of research was employed for the study. A rating scale was used to know the ICT related competencies that teachers need for instructional purpose. The rating scale consisted of 47 items based on four types of teacher competencies namely-Technological ICT Competencies, Pedagogical ICT Competencies, Didactical ICT Competencies and Social ICT Competencies. The sample consisted of 73 teacher educators among which 44 were males and 29 were females. Data was collected through the use of e-mail and by personally contacted the respondents and analysed using frequencies and percentage. Findings of the study reveal that all the teacher educators were agree that the following ICT competencies that teachers need to develop are: (i) Use ICT skills in developing and presenting information; (ii) Prepare ICT-based learning environment, designing effective learning experiences and creating rich learning environments with the support of ICT and Understanding of computer technology can enhance student learning; (iii) Using ICT as a didactical tool in the class as well as implement cooperative learning strategies using ICT. Using ICT as a didactical tool implies using it to establish dynamic and powerful instructional strategies and environment and (iv) Demonstrating knowledge and skills for using technology in ethical, legal and safe ways and to use humour and good manners during the teaching and learning process.